A hydrothermal clay mineral assemblage at the Late Proterozoic unconformity in the Buenos Aires Complex - La Tinta Formation, Barker area, Tandilia Ranges (Argentina) - Martinez, Juan Cruz (2010)
A general alteration pattern of two transitional clay mineral assemblages was determined by petrography and X-ray diffractometry studies at the Tandilia Late Proterozoic unconformity zone, around the Barker locality: (1) K-white mica + chlorite + calcite anatase-rutile secondary quartz (farther from the unconformity) and (2) pyrophyllite + K-white mica + Ti-rich hematite ± aluminium phosphate-sulphate minerals ± tourmaline ± anatase-rutile (closer to the unconformity). The local occurrence of Na in K-white micas and K-Na in pyrophyllite is described for the first time. Possible interlayering with intermediate K-Na mica and paragonite is indicated by detailed X-ray diffraction analyses. A negative Eu anomaly (Eu/Eu* = 0.24), strongly positive Eu anomaly (Eu/Eu* =11.7) and positive Ce anomaly characterized rapid changes from an unaltered basement to the most altered basement and sedimentary rocks at the unconformity. Aluminium phosphate-sulphate minerals dominate patterns of LREE. A model of hydrothermal alteration comparable to that of unconformity-related uranium deposits is presented.